The effects of externalities and framing on bribery in a petty corruption experiment - Barr, A; Serra, D (2008)
Using a simple one-shot bribery game, we find evidence of a negative externality effect and a framing effect. When the losses suffered by third parties due to a bribe being offered and accepted are high and the game is presented as a petty corruption scenario instead of in abstract terms bribes are less likely to be offered. Higher negative externalities are also associated with less bribe acceptance. However, framing has no effect on bribe acceptance, suggesting that the issue of artificiality first raised by Bardsley (2005) may be of particular importance in bribery experiments.